Benzene as a by-product of toluene with methanol transformation on the basic zeolite catalysts and its presumable origin - Yuliya G Voloshyna; Olexandra P Pertko; Serhiy V Konovalov; Lyubov K Patrylak (Adsorption Science & Technology)
The goal of the present study was to clarify the nature of benzene forming in base catalyzed side-chain alkylation of toluene with methanol. Benzene formation has been observed as a primary product in the very beginning of conversion of toluene/methanol mixture on the basic catalysts. Dynamics of alteration of its content in reaction products has been explained. The nature of sites responsible for benzene formation has been suggested considering conception concerning preferences in toluene or methanol adsorption on the catalyst of different basicity. Toluene has been concluded to be a raw material for benzene formation.